A Case Study on Students’ Perception of Drama Activities in Teaching Speaking - Sulastri Manurung (English Department, University of Riau Kepulauan, Batam,Indonesia, 2018)
Students’ perceptions of the language learning have been a fascinating topic for researchers as they can be as reflection for the improvement of the teaching and learning of English especially speaking. The present study aims to investigate the students’ perception of the drama activity in speaking class. It was designed in qualitative research method. The research subject was the fourth semester students of English Department at University of Riau Kepulauan. The data was collected through the content analysis by means of rubric and reflection sheet. With the help of these instruments, the results and the analysis of reflection sheets and rubric reveals the students had positive perception of drama activity in speaking class in terms of building self-confidence, fun, emerging acting skill, improving vocabulary, and building teamwork.